AÃ‡ÃƒO DE BIOESTIMULANTES EM FEIJOEIRO (Phaseolus vulgaris CV.IAC â€“ CARIOCA TYBATÃƒ) - Castro, Paulo Roberto de Camargo; Silva, Gustavo Pinto; Cato, Stella Corsorte; Tavares, SÃlvio (REVISTA DE AGRICULTURA, 2016)
AÇÃO DE BIOESTIMULANTES EM FEIJOEIRO (Phaseolus vulgaris CV.IAC – CARIOCA TYBATÃ)